2016
DOI: 10.5539/ies.v10n1p163
|View full text |Cite
|
Sign up to set email alerts
|

Design, Explanation, and Evaluation of Training Model Structures Based on Learning Organization—In the Cement Industry with a Nominal Production Capacity of Ten Thousand Tons

Abstract: This research aims to determine the effectiveness of training based on learning organization in the staff of cement industry with production capacity over ten thousand tons. The purpose of this study is to propose a training model based on learning organization. For this purpose, the factors of organizational learning were introduced by qualitative research in the form of open codes, axial codes, selective codes and the resulted observations, and then the final model was obtained by structural equation model. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…He observed that a well-defined structure of rules and regulations, compatible culture and knowledge sharing can enhance the learning and decision-making process. Rahimian et al (2016) stated that the structure of the mining industry has a positive impact on the organizational culture and the level of human resources development. In their study, they argued that the roles and responsibilities that are identified in the organizational structure could facilitate the transfer of knowledge which accordingly could enhance building of a LO.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…He observed that a well-defined structure of rules and regulations, compatible culture and knowledge sharing can enhance the learning and decision-making process. Rahimian et al (2016) stated that the structure of the mining industry has a positive impact on the organizational culture and the level of human resources development. In their study, they argued that the roles and responsibilities that are identified in the organizational structure could facilitate the transfer of knowledge which accordingly could enhance building of a LO.…”
Section: Theoretical Backgroundmentioning
confidence: 99%